2016
DOI: 10.1245/s10434-016-5407-9
|View full text |Cite
|
Sign up to set email alerts
|

Operative and Oncologic Outcomes in 9861 Patients with Operable Breast Cancer: Single-Institution Analysis of Breast Conservation with Oncoplastic Reconstruction

Abstract: Patients undergoing BCS + R are not disadvantaged in terms of complications and short-term (3-year) outcomes compared with BCS patients or patients who underwent TM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
100
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(107 citation statements)
references
References 27 publications
6
100
0
1
Order By: Relevance
“…Patients opting for reconstructive procedures (OS or M+R) were most significant with a diagnosis of DCIS. Previous analyses from 1998 to 2011 showed that mastectomy and M+R rates increased most significantly in lower-staged breast cancers characterized by negative nodal involvement, small radius, and non-invasive pathology [8, 12]. Such results correlate with our present findings of surgical reconstruction in patients with DCIS.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Patients opting for reconstructive procedures (OS or M+R) were most significant with a diagnosis of DCIS. Previous analyses from 1998 to 2011 showed that mastectomy and M+R rates increased most significantly in lower-staged breast cancers characterized by negative nodal involvement, small radius, and non-invasive pathology [8, 12]. Such results correlate with our present findings of surgical reconstruction in patients with DCIS.…”
Section: Discussionsupporting
confidence: 90%
“…Although both M+R and OS inherently represent reconstructive techniques, OS has higher patient satisfaction [19, 20] and has also been shown to be cost-effective [23, 24]. Collectively, these fundamental principles may influence a patient’s decision for breast reconstruction, and thereby explain the trends seen in our present analysis [6, 12]. …”
Section: Discussionmentioning
confidence: 86%
“…TM procedures are more complex than standard BCS, with potential resource implications. Although complication rates and oncological safety have been reported in the literature the majority of published studies are retrospective, single‐centre, often single‐surgeon case series with limited follow‐up. Many are poorly designed and reported, with inconsistent end‐points that limit cross‐study comparison and meaningful data synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Since the end of 1900s, when oncoplastic approach began, it has been spreading over breast units, and it has increased notably in the last decade; as an example of this, Carter et al (12) state that the use of oncoplastic breast surgery experimented a nearly fourfold increase in the percentage of all breast cancer surgeries during the study period (2007 to 2014) in a single center study comprising 10,607 operations; 75% of the patients had an early cancer (T1 or T2 tumor) and the rate of positive or close margins was lower for oncoplastic techniques than conventional ones (5.8% vs. 8.3%).…”
Section: Hernanz Et Al Tailored Needle-guided Excisionmentioning
confidence: 99%